(untitled) (مجلة وقف في دراسات الاوقاف, 2026)
Study Methodology: in this study, the researcher used the descriptive method, in its documentary and survey method. Study instrument: The researcher used the questionnaire instrument to gather information. Population and study sample: the study population consists of all the administrative leaders in the universities, the heads of the departments working in Al-Imam Muhammad bin Saud Islamic University in Riyadh, King Saud University in Riyadh, King Fahd University of Petroleum and Minerals in Dhahran, King Abdul Aziz University in Jeddah, and the Islamic University in Madinah; because of their history as they are the oldest universities in the Kingdom of Saudi Arabia; they have an interest in research related to endowments; and they have experience in dealing with endowments, with a total number of (824). The researcher used the comprehensive inventory method and applied the questionnaire to the whole representative population. The researcher designed the questionnaire electronically on (Google Drive), and distributed the questionnaire link to the study population. The number of valid responses for analysis reached (305), representing (37%) of the study population. The researcher also used the method of surveying experts to validate the suggested proposal by a (20) experts, among faculty members in Saudi universities.